DETECTION OF GENETIC POLYMORPHISM OF NAD (P) H: QUINONE OXIDOREDUCTASE 1 (NQO1) AMONG SUDANESE PATIENTS WITH ACUTE LYMPHOID LEUKAEMIA - 2* Mahdi .H. A. Abdalla,1 Safa M. O. Kobar (Journal of Biomedical and Pharmaceutical Research, 2017)
Polymorphic variations of several genes associated with dietary effects and exposure to environmental carcinogens may influence susceptibility to leukemia development. This study aimed to examine the association of NQO1 C609T polymorphism with the risk of acute lymphoid leukaemia (ALL) and the clinical outcome among ALL patients in Sudan. Seventy five newly diagnosed ALL patients were enrolled in this study, their NQO1 C609T genotypes (detected by PCR/RFLP) and haematological feature were determined and compared with 75 age and sex matched normal subjects as control. The study revealed a 2.9-fold increased risk of ALL for those carrying NQO1 609CT (heterozygous) genotype (OR 2.878, P value 0.040). The frequency of NQO1 609 TT (homozygous) genotype was slightly higher among ALL patients with a 1.1 folds than control group, but with no statistical significance (OR 1.096, P value 0.869). We observed a statistically significant reduction in the mean Hb level and RBCs count in patients with mutant genotypes than in wild type patients (p value 0.000 and 0.003), WBCs count was significantly higher in patients with mutant type when compared to those with the wild type (p value 0.000). In conclusion, our results indicate that NQO1 C609T mutant genotypes, with low enzymatic activity, are associated with increased risk of ALL and worse haematological features. Key words: Acute lymphoid leukaemia, NQO1 polymorphism, Sudan.